Territorio e inmigración en España. Análisis de casos en Palma de Mallorca y León - Jesús M. González Pérez (Unité Mixte de Recherche 8504 Géographie-cités, 2004)
Spain has been profoundly transformed by the well-known socio-political and economic changes that have taken place since the end of 1978. In a few short years, the old autocratic State was converted into an important capitalist and liberal economy fully adapted to the commitments of the European Union. Throughout the course of the last decade of the twentieth century, the consequences of full incorporation into the European Union and the effects of globalization contributed to the modification of social structures in the Spanish city of the twenty-first century. Determining economic and cultural factors play a decisive role in the rising numbers of immigrants from Africa, Asia and Latin America, but other geographic factors and factors related to location make Spain an attractive place to settle in for retired seniors from other parts of Europe with medium and high purchasing power. This paper focused in the study of immigration in Spain in different scales. Interregional and interurban analyses are based in two territories with a different socio-economic level and demographic behavior: the Autonomous Communities of Balearic Islands and Castile and León and the cities of Palma de Mallorca and León.